2018
DOI: 10.14421/grieb.2018.061-05
|View full text |Cite
|
Sign up to set email alerts
|

Zakat Fund As The Starting Point Of Entrepreneurship In Order to Alleviate Poverty (SDGs Issue)

Abstract: As known, Indonesia is a nation with the largerst Moslem society in the world. According to data issued by Bappenas, in 2020 the population of Indonesia is predicted about 271,066,400 people (Bappenas: 2018). 85 percent of this population (ca. 230.406.440 people) are Moslems. It shows the huge potential in the acceptance of zakat fund, as an obligation for a Moslem who has qualified in accordance with the provisions of Islam.            Since MDGs declared in 2000 (UNRC: 2008) which contains a commitment to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…They found that in the short term zakat can achieve the SDG of inequality reduction and promote the economic growth of each state. In addition, the potential of zakat funds to finance SDGrelated projects was addressed by Asmalia et al (2018) and Harahap (2018). Their research respectively studied the possibility of zakat funding of SDGs and entrepreneurship.…”
Section: Previous Scholarly Work On Zakat and Sdgsmentioning
confidence: 99%
“…They found that in the short term zakat can achieve the SDG of inequality reduction and promote the economic growth of each state. In addition, the potential of zakat funds to finance SDGrelated projects was addressed by Asmalia et al (2018) and Harahap (2018). Their research respectively studied the possibility of zakat funding of SDGs and entrepreneurship.…”
Section: Previous Scholarly Work On Zakat and Sdgsmentioning
confidence: 99%
“…In economics, zakat aims to influence several parameters, including aggregate consumption, savings and investment, aggregate labour and capital supply, poverty elimination, and economic growth. Paying zakat demonstrates concern for the least fortunate people of society (Harahap, 2018). Offering contributions to the poor and needy will contribute to economic growth by channelling capital to members of society with a far greater marginal propensity to consume.…”
Section: Introductionmentioning
confidence: 99%
“…Zakat is one of Islam's five pillars. Zakat refers explicitly to growth and expansion (Harahap, 2018). Based on surah al-Baqarah verse 43, paying zakat, the third pillar of Islam, is mandatory for every Muslim who has satisfied the qualifications to cleanse their possessions by distributing the zakat to the beneficiaries.…”
Section: Introductionmentioning
confidence: 99%